Electrochemistry of carbon electrodes (Advances in electrochemical science and engineering, 2016)
The book sets the standard on carbon materials for electrode design. For the first time, the leading experts in this field summarize the preparation techniques and specific characteristics together with established and potential applications of the different types of carbon-based electrodes. An introductory chapter on the properties of carbon together with chapters on the electrochemical characteristics and properties of the different modifications of carbon such as carbon nanotubes, graphene, carbon fiber, diamond or highly ordered pyrolytic graphite provide the reader with the basics on this fascinating and ubiquitous electrode material. Cutting-edge technologies such as carbon electrodes in efficient supercapacitors, Li-ion batteries and fuel cells, or electrodes prepared by screen-printing are discussed, giving a complete but concise overview about the topic. The clearly structured book helps newcomers to grasp easily the principles of carbon-based electrodes, while researchers in fundamental and applied electrochemistry will find new ideas for further research on related key technologies